Pengaruh Digital Marketing Dan Celebrity Endorsement Terhadap Keputusan Pembelian Produk Erigo di Kota Cirebon - Syifa Milia Kerin; Anwar Musadad (Peneliti.net, 2022)
This study aims to determine, analyze, and explain how the partial and simultaneous influence of digital marketing and celebrity endorsement on purchasing decisions for erigo products in Cirebon City. This research uses quantitative research with descriptive and verification methods. The population in this study are consumers who have bought products from Erigo at least once. The sample tested in this study amounted to 384 people using the Isaac & Michael sampling method. This research uses non-probability sampling technique with purposive technique. The data analysis technique used scale range analysis and path analysis with SPSS 26 software analysis tool for Windows.Based on the results of the research that has been done. The correlation coefficient between digital marketing and celebrity endorsement variables is 0.527 which is at a relatively moderate level of correlation, quite strong. The partial effect of digital marketing (X1) on purchasing decisions has a greater value than the celebrity endorsement variable (X2), which is 16.9% while the celebrity endorsement variable simultaneously has a contribution of 9%, simultaneously the total influence of digital marketing and celebrity endorsement on the decision purchase of 38.9% while the remaining 61.1% influenced by other factors outside the scope of research in this study.